Hyperpolarized Xenon-129: A New Tool to Assess Pulmonary Physiology in Patients with Pulmonary Fibrosis - Kun Qing; Talissa A. Altes; John P. Mugler; Jaime F. Mata; Nicholas J. Tustison; Kai Ruppert; Juliana Bueno; Lucia Flors; Yun M. Shim; Li Zhao; Joanne Cassani; William G. Teague; et al. (Biomedicines, 2023)
Purpose: The existing tools to quantify lung function in interstitial lung diseases have significant limitations. Lung MRI imaging using inhaled hyperpolarized xenon-129 gas (129Xe) as a contrast agent is a new technology for measuring regional lung physiology. We sought to assess the utility of the 129Xe MRI in detecting impaired lung physiology in usual interstitial pneumonia (UIP). Materials and methods: After institutional review board approval and informed consent and in compliance with HIPAA regulations, we performed chest CT, pulmonary function tests (PFTs), and 129Xe MRI in 10 UIP subjects and 10 healthy controls. Results: The 129Xe MRI detected highly heterogeneous abnormalities within individual UIP subjects as compared to controls. Subjects with UIP had markedly impaired ventilation (ventilation defect fraction: UIP: 30 ± 9%; healthy: 21 ± 9%; p = 0.026), a greater amount of 129Xe dissolved in the lung interstitium (tissue-to-gas ratio: UIP: 1.45 ± 0.35%; healthy: 1.10 ± 0.17%; p = 0.014), and impaired 129Xe diffusion into the blood (RBC-to-tissue ratio: UIP: 0.20 ± 0.06; healthy: 0.28 ± 0.05; p = 0.004). Most MRI variables had no correlation with the CT and PFT measurements. The elevated level of 129Xe dissolved in the lung interstitium, in particular, was detectable even in subjects with normal or mildly impaired PFTs, suggesting that this measurement may represent a new method for detecting early fibrosis. Conclusion: The hyperpolarized 129Xe MRI was highly sensitive to regional functional changes in subjects with UIP and may represent a new tool for understanding the pathophysiology, monitoring the progression, and assessing the effectiveness of treatment in UIP.